MENYOAL HUKUMAN MATI DALAM ISLAM (SEBUAH TINJAUAN DARI AYAT DAN HADIS) - Daipon, Dahyul (Alhurriyah, 2015)
There are a couple of Regulation Legislation concerning the death penalty for a criminal offense in Indonesia. Act like No.7/Drt/1955 on Economic Crime, Law no. 22 of 1997 concerning the Crime Narcotics and Psychotropic Substances, Law no. 31 of 1999 as amended by Law no. 20 of 2001 on the Corruption, Law no. 26 of 2000 concerning the Crime Against Human Rights, Government Regulation Anti-Terrorism Act which was passed into law. There are two camps that emerged in the application of the death penalty; The first is a faction who opposed the application of the death penalty in law in Indonesia, with a variety of reasons that mostly associated with human rights abuses (human rights) the right to life. On the basis of Article 28A of the 1945 Constitution which states "every person has the right to live and to defend life and living" and foreign treaties, such as the International Covenant on Civil and Political Rights (ICCPR), which regulates the right to life (right to life), which states in article 6 ayat1 "every human being has the right to live and gets right to the protection of the law and no one can deprive it". The second camp is a positive law in Indonesia itself. There are many laws and regulations in Indonesia that still apply the death penalty within its provisions. This was affirmed by a statement in explanation of Article 9 (1) of Law no. 39 of 1999 on Human Rights which basically restricts the right to live in two respects, namely abortion for the sake of her mother's life and is based on a court decision in a death penalty case. Apart from the above polemic, when associated with Islamic law, in fact in the Qur'an and Hadith have set the death penalty for criminals who consequently superb as mentioned. As against perpetrators hirabah, qishas penalty for murder, criminal adultery, rebellion and apostasy.